(untitled) (Altre Modernità, 2015)
As Eric Hobsbawm has highligted, “immagined community of millions often seems more real as a team of eleven players […] The individual, even the one who only cheers, becomes a symbol of his nation himself””. That is why many national goverments have used sport as a tool for nation building. There is one political actor, however, which would appear not to have drawn any advantage from the symbolic power of sport: the European Union. By referring to the literature on the subjetct and some archival research, the author seek to pin down the reasons behind this distance between sport and the idea of Europe, calling for the creation of an European team in different sporting disciplines in the future that may make up for this lack of common European action.-Abstract in lingua inglese: As Eric Hobsbawm has highligted, “immagined community of millions often seems more real as a team of eleven players […] The individual, even the one who only cheers, becomes a symbol of his nation himself””. That is why many national goverments have used sport as a tool for nation building. There is one political actor, however, which would appear not to have drawn any advantage from the symbolic power of sport: the European Union. By referring to the literature on the subjetct and some archival research, the author seek to pin down the reasons behind this distance between sport and the idea of Europe, calling for the creation of an European team in different sporting disciplines in the future that may make up for this lack of common European action.